2015
DOI: 10.1155/2015/520128
|View full text |Cite
|
Sign up to set email alerts
|

Balance Dysfunction in Parkinson’s Disease: The Role of Posturography in Developing a Rehabilitation Program

Abstract: Balance dysfunction (BD) in Parkinson's disease (PD) is a disabling symptom, difficult to treat and predisposing to falls. The dopaminergic drugs or deep brain stimulation does not always provide significant improvements of BD and rehabilitative approaches have also failed to restore this condition. In this study, we investigated the suitability of quantitative posturographic indicators to early identify patients that could develop disabling BD. Parkinsonian patients not complaining of a subjective BD and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 49 publications
2
27
0
4
Order By: Relevance
“…We found that MPS was present in 31.1% of our cohort, consistent with prevalence estimates of 15–40% in older community-dwelling individuals [25]. A previous study showed impairments in postural sway along the mediolateral axis in Parkinson’s disease patients before the onset of clinical balance dysfunction symptoms [29]. We did not find MPS to be associated with posturography tasks in our study and presence of MPS did not attenuate the associations of regions of interest in the linear regression model (data not shown).…”
Section: Discussionsupporting
confidence: 88%
“…We found that MPS was present in 31.1% of our cohort, consistent with prevalence estimates of 15–40% in older community-dwelling individuals [25]. A previous study showed impairments in postural sway along the mediolateral axis in Parkinson’s disease patients before the onset of clinical balance dysfunction symptoms [29]. We did not find MPS to be associated with posturography tasks in our study and presence of MPS did not attenuate the associations of regions of interest in the linear regression model (data not shown).…”
Section: Discussionsupporting
confidence: 88%
“…Other results were in agreement with our study, Others suggest that early rehabilitation treatment aimed to improve the balance control by several mechanisms have to include (a) stretching exercises to minimize the stiffness of the ankle, (b) a weight-shift training program, to improve balance control, (c) a proprioceptive-motor training, and (d) a balance training based on visual and auditory feedback [31]. Also, others found that gait training with visual cues for one month was successful in improvement in gait speed and step length and increasing the stability of the motor system [32].…”
Section: Discussionsupporting
confidence: 92%
“…This method can provide a visual representation of postural instability which is more objective than other methods and provided in real-time. 15,16 The balance assessment consists of static and dynamic stability measures which provide a foundation for characterizing patients' postural and balance instability. 17,18 Previous research suggests static stability may be correlated with disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Previous research suggests static stability may be correlated with disease severity. 15 In addition, ataxia patients may experience poor body control in dynamic balance. 19 However, the possible patterns of balance dysfunction used in posturography have not been thoroughly studied in SCA3 and the relationship between balance dysfunction and SCA3 phenotype remains unclear.…”
Section: Introductionmentioning
confidence: 99%